Optimizing the Role of Parents in Internalizing the Islamic Education Values of the Alpha Generation in the Digital Era - Mubarok, Ahmad Aly Syukron Aziz Al (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
Technological advances have created its own challenges for parents in educating their children. The number of child abductions accompanied by the excessive use of gadgets by the alpha generation children, poses a challenge for parents to be able to choose methods or ways to internalize Islamic educational values that are able to attract the attention of their children. This article discusses alternative models for internalizing the values of Islamic education by prioritizing optimizing the role of parents. The digital era is troubling many parents who are not familiar with technology. The method in this research is using qualitative research with a phenomenological approach starting from observations in the Medali Village environment, interviews with 2 parents, 2 children, and documentation. The results obtained are in line with expectations which show that Alphan generation children are able to internalize the value of politeness towards adults, peers and the surrounding community, children obey their parents' orders by playing with cellphones at least and the harmony of a child becomes visible and real. The aim of this research is to optimize the important role of parents in the Medali village community in terms of internalizing the values of Islamic education through the values of politeness and harmony in the Alpha generation.